THE URGENCY OF CHARACTER EDUCATION IN IMPROVING STUDENT DISCIPLINE IN MADRASAH - Firdausiyah, Nadiatul; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Globally, character education is crucial for students worldwide to meet the demands of modern times. MAN 1 Probolinggo is one of the schools that is not exempt from problems related to students' character. Therefore, there is a need for character education in improving student discipline. Disciplinary character education must be done continuously from early age to adulthood. The application of disciplinary education will be maximized if supported and through cooperation from various parties. The research uses qualitative description. Data collection through interviews, observations, and documentation. Data analysis uses data aggregation, reduction, presentation, and conclusion drawings. Then, the data's validity is verified through source triangulation and triangulation techniques. This research has obtained the following result: 1) The effort to cultivate character education in improving the discipline of students in MAN 1 Probolinggo is by establishing regulations of the conditioning program, which are orderly arrangements and cultivation activities. 2) The impact of character education in improving student discipline in MAN 1 Probolinggo is to direct students to moral education and discipline them to be more responsible